2017
DOI: 10.1016/j.ijheatmasstransfer.2016.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Rotating metal foam structures for performance enhancement of double-pipe heat exchangers

Abstract: In order to enhance the amount of heat transported in a double-pipe heat exchanger, a compound enhancement is proposed incorporating both active and passive methods. The first one is through introducing secondary flows in the vicinity of the conducting surface using metal foam guiding vanes, which are fixed obliquely and rotating coaxially to trap fluid particles while rotation and then force them to flow over the conducting surface. The other is via covering the conducting surface between the two pipes with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Furthermore, Chen et al [20] observed that despite the increase occurred in the pressure drop, using metal foams results in a remarkable heat transfer enhancement (by as much as 11 times), which leads to a considerable improvement in the comprehensive performance, that is, up to 700%. More recently, an innovative double-pipe heat exchanger was proposed [21,22] through using rotating metal foam guiding vanes fixed obliquely to force fluid particles to flow over the conducting surface while rotation. Furthermore, the conducting surface itself was covered with a metal foam layer to improve the heat conductance across it.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Chen et al [20] observed that despite the increase occurred in the pressure drop, using metal foams results in a remarkable heat transfer enhancement (by as much as 11 times), which leads to a considerable improvement in the comprehensive performance, that is, up to 700%. More recently, an innovative double-pipe heat exchanger was proposed [21,22] through using rotating metal foam guiding vanes fixed obliquely to force fluid particles to flow over the conducting surface while rotation. Furthermore, the conducting surface itself was covered with a metal foam layer to improve the heat conductance across it.…”
Section: Applicationsmentioning
confidence: 99%
“…To optimize the performance achieved, an overall performance system factor, that is, OSP, was introduced as the ratio of the heat exchanged to the total pumping power required. Overall, the negligibly small pumping power required compared to the amount of heat exchanged makes the overall performance of such heat exchangers incomparable, that is, OSP = O( 10 2 )( Figure 3) (Alhusseny et al [22]). It was also observed that while increasing the temperature difference from 30 to 300 C, the overall performance achieved can be improved up to 200-300% depending on the Re* value.…”
Section: Applicationsmentioning
confidence: 99%
“…Such unique hydrothermal features are already in the DNA of either open-core foams formed from highly conductive materials such as metal-or graphite foams (Alhusseny, Al-Fatlawi, et al, 2021). Open-cell metal foams have, for instance, been successfully employed in diversity of thermal applications including heat exchangers (Alhusseny, Turan and Nasser, 2017), latent heat thermal energy storage units (Alhusseny et al, 2020), and the cooling of turbine blades (Al-Aabidy, as well as electrical generators (Alhusseny et al, 2015). On the other hand, the ORNL graphite foams that predominantly possess spherical pores have the potentials to fulfil most of the above-mentioned requirements desirable in thermal management applications .…”
Section: Introductionmentioning
confidence: 99%
“…Alhusseny et al [16] investigated numerically a double-pipe heat exchanger partially filled with high porosity metal foam and rotating coaxially. The heat transfer improvement was obtained by an active method and a passive method.…”
Section: Introductionmentioning
confidence: 99%